Alternate-day modified fasting diet improves weight loss, subjective sleep quality and daytime dysfunction in women with obesity or overweight: a randomized, controlled trial - Hooshiar, Saeedeh Hosseini; Yazdani, Akram; Jafarnejad, Sadegh (Frontiers in Nutrition, 2023)
Background: Both sleep time and quality can be associated with overweight or obesity. In obese people, visceral fat tissue develops, which results in an increment in the production of cytokines. The increased production of inflammatory cytokines can disturb the sleep/wake cycle. Therefore, weight loss by reducing fat tissue can improve sleep disorders. Intermittent fasting diets are popular and effective diets that can decrease body weight and improve anthropometric data and body composition. The present study aimed to evaluate the effect of Alternate-day Modified Fasting (ADMF) on sleep quality, body weight, and daytime sleepiness. Methods: Classification of 56 obese or overweight women, based on age and body mass index (BMI), was done using stratified randomization. Then individuals were assigned to the ADMF group (intervention) or Daily Calorie Restriction (CR) group (control) using the random numbers table for 8 weeks. We measured the Pittsburgh sleep quality Index (PSQI), weight, BMI, and the Epworth sleepiness scale (ESS) as primary outcomes and assessed subjective sleep quality (SSQ), sleep latency, sleep disturbances, habitual sleep efficiency, daytime dysfunction, and sleep duration as secondary outcomes at baseline and after the study. Results: Following an ADMF diet resulted in a greater decrease in weight (kg) (-5.23(1.73) vs -3.15(0.88); P <0.001) and BMI (kg/m2) (-2.05(0.66) vs -1.17(0.34); P <0.001) compared to CR. No significant differences were found in the changes of PSQI (-0.39 (1.43) vs -0.45 (1.88); P= 0.73) and ESS (-0.22(1.24) vs -0.54(1.67); P= 0.43) between 2 groups. Also, following the ADMF diet led to significant changes in SSQ (-0.69(0.47) vs -0.08(0.40); P= <0.001), and daytime dysfunction (-0.65(0.57) vs 0.04(0.75); P: 0.001) in compare with CR diet. Conclusions: These results suggested that an ADMF could be a beneficial diet for controlling body weight and BMI. The ADMF diet didn’t affect PSQI and ESS in women with overweight or obesity but significantly improved SSQ and daytime dysfunction. Trial registration: The Iranian Registry of Clinical Trials (IRCT20220522054958N3), https://www.irct.ir/trial/64510